THE INFLUENCE OF THE QUALITY OF PADANG CUISINE AT PUTRA MINANG RESTAURANT ON PURCHASE INTEREST IN CILEDUG COMMUNITY, TANGERANG CITY, BANTEN PROVINCE - Amrullah Amrullah (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of the quality of Padang cuisine at Putra Minang Restaurant on purchase interest of the people of Ciledug, Tangerang City, Banten Province. This type of research is descriptive quantitative with a simple regression method. A sample of 100 respondents used accidental sampling with a questionnaire distribution technique with a Likert scale from 1 to 5. The results showed that the quality of Padang cuisine at Putra Minang Restaurant has a significant effect on the purchase interest of the Ciledug people because of the way Padang cuisine creates a spicy, savory taste. and is prepared deliciously, then the equipment used is very complete, sufficient and hygienic, and the hands used are very clean, usually the dishes are made by two people with the same recipe, producing a taste of food that is characteristic of the Minangkabau area, which is of high quality and good quality. It is also hoped that Putra Minang Restaurant will always pay attention to the quality of the ingredients to be processed and the cleanliness of the kitchen. In terms of service, smiles and friendliness are needed to please customers